A review of active packaging in bakery products: Applications and future trends. (August 2021) - Qian, Mengyan; Liu, Donghong; Zhang, Xinhui; Yin, Zhongping; Ismail, Balarabe B.; Ye, Xingqian; Guo, Mingming
Abstract: Background: Rapid socio-economic development has allowed bakery products to gradually become a significant portion of people's daily diet throughout the world. However, microbial contamination and oxidation of lipids, as well as proteins in bakery products, may cause substantial economic losses and even threaten human health. The quality and safety properties of bakery products are highly dependent on packaging materials and technologies. Scope and approach: The research into active packaging is a tremendous breakthrough towards solving these economic and safety problems while at the same time providing innovative methods to extend the shelf-life of bakery products. This article reviewed the factors affecting bakery products' shelf-life and highlighted the different active packaging materials with myriad applications in bakery products, including antimicrobial, antioxidant, ethanol emitters and moisture absorbers packaging. Furthermore, consumer preferences towards active packaging, as well as the challenges and future trends in the development of active packaging in the bakery industry were also discussed. Key findings and conclusions: By absorbing or releasing active compounds, active packaging systems can effectively delay or prevent microbial spoilage, reduce oxidation, and enhance the safety and quality of bakery products. Some innovative materials, such as stimuli-responsive antimicrobial materials, should be considered to successfully implement active packaging solutions in the bakery industry. Graphical abstract: Graphical summary of the application of active packaging in bakery products. Image 1 Highlights: 1. A review of applications and prospects of active packaging (AP) in bakery products. 2. Oxidation and microbial contamination cause bakery products deterioration. 3. AP can release active agents into packaged food or absorb substances from headspace. 4. Stimuli-responsive antimicrobial materials have great potential application in AP. 5. AP enhances the quality and safety of bakery foods and extends their shelf-life.